Hemeroteca do NUT-SECA: da origem à atualidade - Farias, Maria Lúcia Maranhão de (2013)
The general objective of this research is to (re)constitute the memory of the newspaper library at NUT-SECA, in the period of 1980-2012, as a support for future historiographies, and also, to contribute to the dissemination of information existing in the various thematic collections. It results from a descriptive research intending to build a history that emphasizes the diversity of content and the conditions of conservation, preservation and social use of the newspaper library as an artifact of information. The methodology has a quantitative-qualitative approach and uses documentary research to prepare the documents for data collection. For data analysis two techniques were applied: the Documentary Analysis (AD) and Content Analysis (CA). The results presents that the newspaper library collection at NUT- SECA is a historical documentation, as well as one of the memory locations of the drought and of Brazil s northeastern semi-arid, especially in Rio Grande do Norte, and that, depending on use, may contribute to the production of specific knowledge, strengthening the scientific literature on the theme of drought and general research in the field of Social Sciences. The final considerations are expected to have contributed to the construction of new knowledge about the newspaper library at NUT-SECA, as well as we hope the wide socialization of its collection to be a support for historiographies regarding this issue and/or on issues surrounding the NUT -SECA and its newspaper library